THE INTELLECTUAL INTELLIGENCE IN EARLY CHILDHOOD : A SYSTEMATIC LITERATURE REVIEW - Fairuz Rizka Ghazalah (OPTIMA: Journal Of Guidance and Counseling, 2021)
Talking about human intelligences, there are 3 things that will be discussed, there are IQ (intelligence quotient), EI (emotional intelligence) and SI (spiritual intelligence). From the three things above, there is only one thing will be discussed in this paper, it is the IQ (intelligence quotient) also known as intellectual intelligence. Specifically, this paper will be discussed the intellectual intelligence in early childhood using literature study method. Early childhood also known as the golden age, which means in this periods humans grow and develop rapidly. One Arabic proverb says “alwaladu kal warakatil bayda taktubu fii haa maa tasyaa” means a child is like clean white sheet that we can write anything on it. In the golden age, humans absorb information very quickly, some studies say that the golden age is the right time to do the optimizing various types of intelligence in humans, one of which is the optimization of intellectual intelligence.